Driving corporate sustainability through Green Financial Management: The mediating role of green competitive advantage in Indonesian MSMEs - Andi Amri; Narto Irawan Otoluwa; Bahtiar Herman (Journal of Management Small and Medium Enterprises (SMEs), 2026)
The increasing emphasis on sustainable business practices has encouraged micro, small, and medium enterprises (MSMEs) to adopt environmentally oriented financial strategies as a source of long-term competitiveness. This study examines the influence of Green Financial Management, comprising Green Investment Decisions, Green Budgeting, and Green Disclosure on Corporate Sustainability Performance among Indonesian MSMEs, while investigating the mediating role of Green Competitive Advantage. A quantitative research design was employed using primary data collected through a structured survey of 415 owners and managers of manufacturing and agro-industry MSMEs across Indonesia. The findings indicate that all dimensions of Green Financial Management significantly and positively contribute to Corporate Sustainability Performance. Moreover, Green Competitive Advantage plays a pivotal mediating role by strengthening the relationship between green financial practices and sustainability outcomes, explaining approximately 68.5% of the variance in Corporate Sustainability Performance. These results suggest that green financial initiatives should be viewed not as compliance-related costs but as strategic investments that enhance firms’ competitive positioning and sustainability capabilities. The study extends the literature on sustainable finance and MSME competitiveness by providing empirical evidence from an emerging economy context, highlighting the strategic value of integrating environmental considerations into financial decision-making. Although the study is constrained by its cross-sectional design, the findings offer important implications for policymakers and business practitioners seeking to promote sustainable and competitive MSME development in Indonesia. Future research is encouraged to adopt longitudinal approaches to capture the dynamic effects of green financial strategies on organizational resilience and sustainable growth. Keywords: Green Financial Management; Green Competitive Advantage; Indonesia Corporate Sustainability Performance; MSMEs